An Analysis of Culturally Specific Items and Translation Techniques Applied in Edensor - Prima Busana; Agus Subiyanto (Yayasan Visi Intan Permata, 2020)
This research aims to identify and classify Culturally Specific Items (CSIs) of a bilingual novel titled Edensor by using Newmark’s taxonomy and to analyze CSIs classification by using translation techniques of Mollina and Albir. Further, this research purposes to know the accurateness of the translation. This research design is conducted with a qualitative-descriptive approach. The data of the research are taken from a novel namely Edensor which is written by Andrea Hirata, and the novel is translated from Indonesian to English by John Colombo. The researchers collect the data by using techniques of library research. The data is collected by identifying and classifying of CSIs in the novel. Then, the data is analyzed based on the translation techniques. The results show that amplification technique is used for 16 data (48.49%), borrowing technique is used for 6 data (18.18%), calque technique is used for 2 data (6.06%), description technique is used for 1 data (3.03%), generalization technique is used for 7 data (21.21%), and reduction technique is used for 1 data (3.03%). The mostly used in translation technique of CSIs is amplification technique by giving additional information, because it can make a clear for the English readers. Further, the accurateness of the CSIs translation shows 19 data (57.58%) for accurate translation, 10 data (30.30%) for less-accurate translation, and 4 data (12.12%) for inaccurate translation.